Stress and neonatal massage: Effects of massage in the stress of pre-term neonate - da Silva Freitas, Otília Maria (2012)
This experimental study evaluated the effects of the massage on stress in preterm neonates that were hospitalised in neonatal intermediate care units. The sample consisted of 32 healthy and clinically stable premature neonates, hospitalised in Portuguese units of intermediate neonatal care. The premature neonates were randomly distributed in two groups - control and experimental - with 16 neonates in each group. The groups did not display statistically significant differences in basic features, thus forming equivalent groups. During the study both groups received the same pattern of neonatal care, in addition, the experimental group also received the massage. Stress levels were evaluated by measuring the levels of cortisol, norepinephrine and epinephrine (neuroendocrine catecholamines) samples of blood and urine obtained on the first and last day of the study. There was no statistically significant difference in the levels of cortisol in the urine between groups or between the first and last day. As far as the levels of cortisol and urine are concerned, we evidenced that there are not significant differences between the groups or the moments and that both the effect of the interaction between the group and the time is not statistically significant. Concerning the levels of cortisol in the blood, we verified that the effect of time is statistically significant with p <0.001. The levels of cortisol in the blood of the preterm neonates from both groups were identical at the two moments and a similar reduction occurred from the first to the second moment. In the experimental group as well as in the control group the differences from the first to the second moment are statistically significant whit p=0.001 and p=0.004, respectively. In regards to the levels of urinary norepinephrine, the effects of group, time, and interaction between the two variables were not statistically significant. As for the levels of norepinephrine in the blood, we verified the existence of a significant effect (p=0.040) in the group, however the effects of time or interaction were not significant. The experimental group demonstrated inferior levels of norepinephrine in the blood at all times; and the increase between the first moment to the second was statistically significant for the experimental group (p=0.002) and for the control group (p=0.004). Neither urinary or blood epinephrine levels varied in a statistically significant fashion when comparing groups, time, or the interaction between those two variables. We conclude that the effect of massage on the stress of healthy and medically stable preterm newborns admitted to neonatal intermediate care unit was not statistically significant.